Quality benchmarking of smartphone laboratory medicine applications: comparison of laboratory medicine specialists’ and non-laboratory medicine professionals’ evaluation - Jovičić, Snežana; Siodmiak, Joanna; Alcorta, Marta Duque; Kittel, Maximilian; Oosterhuis, Wytze; Aakre, Kristin Moberg; Jørgensen, Per; Palicka, Vladimir; Kutt, Marge; Anttonen, Mikko; Velizarova, Mileva Georgieva; Marc, Jania (Clinical chemistry and laboratory medicine, 2021)
Objectives There are many mobile health applications (apps) now available and some that use in some way laboratory medicine data. Among them, patient-oriented are of the lowest content quality. The aim of this study was to compare the opinions of non-laboratory medicine professionals (NLMP) with those of laboratory medicine specialists (LMS) and define the benchmarks for quality assessment of laboratory medicine apps. Methods Twenty-five volunteers from six European countries evaluated 16 selected patient-oriented apps. Participants were 20-60 years old, 44% were females, with different educational degrees, and no professional involvement in laboratory medicine. Each participant completed a questionnaire based on the Mobile Application Rating Scale (MARS) and the System Usability Scale, as previously used for rating the app quality by LMS. The responses from the two groups were compared using the Mann-Whitney U test and Spearman correlation. Results The median total score of NLMP app evaluation was 2.73 out of 5 (IQR 0.95) compared to 3.78 (IQR 1.05) by the LMS. All scores were statistically significantly lower in the NLMP group (p<0.05), except for the item Information quality (p=0.1631). The suggested benchmarks for a useful appear: increasing awareness of the importance and delivering an understanding of persons’ own laboratory test results; understandable terminology; easy to use; appropriate graphic design, and trustworthy information. Conclusions NLMP’ evaluation confirmed the low utility of currently available laboratory medicine apps. A reliable app should contain trustworthy and understandable information. The appearance of an app should be fit for purpose and easy to use.